Estudio de la publicidad de Saga Falabella desde el punto de vista de los niveles socioeconómicos B y C de Lima metropolitana: Patrones de identificación y rechazo - Cornejo Mendoza, Claudia Gretel (2021)
The general objective of this study was to identify the perception of consumers be longing to socioeconomic levels "B" and "C" of Lima Metropolitana about the Saga Falabella’s advertising campaigns. The methodology that was carried out for this study was descriptive and presented a mixed-methods. Likewise, the sample was made up of consumers from socioeconomic levels "B" and "C". To carry out the present study, we used, on the one hand, the survey technique, with a sample of 100 people and, secondly, the interview technique, with a sample of 10 people. As a result of the execution of the investigation, it was determined that Peruvian con sumers of Levels "B" and "C" perceive Saga Falabella's advertising as elitist, basic and not very representative, because it uses stereotypes that generate a certain distance and little identification within the Peruvian context.